The Influence of Work Motivation and Work Discipline on Employee Performance with Work Engagement as a Mediating Variable - Edhy Richard; Restu Alam Paripurnawaty; Chonchita Valentina Latupapua; Agusthina Risambessy (LP2M IAIN Palopo, 2026)
This study investigates the influence of work motivation and work discipline on employee performance, with work engagement as a mediating variable in a government law enforcement institution. Grounded in motivational theory—including Self-Determination Theory, Goal-Setting Theory, and Equity Theory—and supported by established frameworks on work discipline and employee engagement, this research develops seven hypotheses relating these constructs. A quantitative explanatory design was employed, collecting data from 125 respondents selected through proportional random sampling using the Slovin formula from a population of 182 employees. Structural Equation Modeling based on Partial Least Squares (SEM-PLS) was used for data analysis. Results indicate that: (1) work motivation positively and significantly influences work engagement; (2) work motivation does not significantly influence employee performance directly; (3) work discipline positively and significantly influences work engagement; (4) work discipline positively and significantly influences employee performance; (5) work engagement does not significantly influence employee performance; (6) work engagement does not mediate the relationship between work motivation and performance; and (7) work engagement does not mediate the relationship between work discipline and performance. These findings suggest that in bureaucratic, rule-based organizations, formal discipline exerts a more dominant direct effect on performance than psychological engagement. The study contributes to human resource management theory by contextualizing motivational constructs within institutional settings.